Effect of early and current Helicobacter pylori infection on the risk of anaemia in 6.5-year-old Ethiopian children - Taye, Bineyam; Enquselassie, Fikre; Tsegaye, Aster; Amberbir, Alemayehu; Medhin, Girmay; Fogarty, Andrew W.; Robinson, Karen; Davey, Gail (BioMed Central, 2015)
Background